STUDIES ON THRESHOLD CURRENT DENSITIES FOR CONVULSION OF FISH USING A SQUARE WAVE STIMULATOR - BISWAS, K P (Fishery Technology, 2025)
The threshold current densities and volltage tensions (bodyvoltages) between the head and tail for bringing about distinctreactions in Salmo irideus, Cyprinus Carpio, Tinea tinea,Gasterosteus aculeatus and Salmo fario were studied. In C. carpioand T. tinea, absolute current densities required decreased withincrease in length of fish. Threshold current densities for differentreactions of fish increased with rise in water temperature andconductivity of surrounding medium except in case of T. tineawhere low current densities were sufficient in higher conductivityof water. Impulse D. C. was superior to continuous D. C.Better effect was noticed in fishes in lower current densities whentheir bodies were parallel to the lines of current conduction.